Laryngostroboscopic and acoustic analysis findings in patients with vocal nodules and patients with functional dysphonias in Galicia - Halawa, Wasim Elhendi (2012)
Objective: To evaluate the laryngostroboscopic and acoustic analysis findings in patients with vocal nodules and functional dysphonias in Galicia.Patients and Methods: 97 patients diagnosed of vocal nodules and 65 patients diagnosed of functional dysphonisa were examined by laryngostroboscopy, following a standardized protocol which includes: analysis of glottal closure, vocal fold vibration and the mucosal wave. For acoustic analysis we used the program Dr. Speech Science evaluating the mean fundamental frequency (F0) and its standard deviation, jitter, shimmer, and Normalized Noise Energy (NNE).Results: All patients showed alteration of at least one laryngostroboscopic parameter. Acoustic analysis indicated that most patients showed a reduction of fundamental frequency, an increase of perturbation (jitter and shimmer), and an increase of NNE.Conclusion: Laryngostroboscopy, systematized through a protocol, is a very useful technique for the diagnosis of structural and functional abnormalities in patients with vocal nodules and functional dysphonia, while acoustic analysis of voice can be useful as a complementary tool in the diagnosis of these patients.